Erythrocyte size as diagnostic character for the identification of live cryptic Odontophrynus americanus and O. cordobae (Anura: Cycloramphidae) - Grenat, P.; Salas, N. E.; Martino, A. L. (Zootaxa, 2009)
External morphology and size do not allow a distinction between diploid Odontophrynus cordobae and tetraploid O. americanus (Beçak et al. 1967; Barrio and Pistol de Rubel 1972). In Córdoba province allopatric diploid populations are distributed to the NW and allopatric tetraploid populations to the SE. Sympatric populations would occur in the SW of the province. A diagnostic character should be found for a correct, simple and rapid distinction of the species without sacrificing individuals. Differences in erythrocyte size (ES) between diploid and tetraploid Odontophrynus were found (Rosset et al. 2006). Martino & Sinsch (2002) defined a range of erythrocyte area for O. cordobae and O. americanus but individuals were not cytogenetically studied. Rosset et al. (2006), showed cell areas from only 2 preserved museum specimens of O. cordobae.